In vitro reconstitution of eukaryotic ion channels using droplet interface bilayers. - Leptihn, S; Thompson, JR; Ellory, J; Tucker, S; Wallace, M (2011)
The ability to routinely study eukaryotic ion channels in a synthetic lipid environment would have a major impact on our understanding of how different lipids influence ion channel function. Here, we describe a straightforward, detergent-free method for the in vitro reconstitution of eukaryotic ion channels and ionotropic receptors into droplet interface bilayers and measure their electrical activity at both the macroscopic and single-channel level. We explore the general applicability of this method by reconstitution of channels from a wide range of sources including recombinant cell lines and native tissues, as well as preparations that are difficult to study by conventional methods including erythrocytes and mitochondria.